Authorship as a research topic in Brazilian Information Science: conceptual analysis (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This research aims to identify scientific articles indexed in the Information Science Database containing the word authorship in the title. The methodology used descriptive, exploratory and bibliographic research, with scientometric and qualitative-quantitative approaches. Sixty articles were collected and of these, only nine were analyzed because they had definitions of “authorship”. The absence of the concept of “authorship” demonstrates that it is a consolidated notion, evidencing “silent relationships” that do not require conceptual explanation. The results indicated that the definitions have characteristics of similar aspects with diffuse attributes that lead to confusion between “authorship”, as a process, and the author, as the subject of the action.
Keywords: authorship; Information Science; notions of authorship; conceptual definition; intellectual responsibility